ON THE MULTICULTURALISM PROJECT AND THE SOCIOPOLITICAL STATUS OF ISLAM IN UKRAINE Preliminary Theses for a Case Study of Ethnocultural, Confessional, and Personal Self-Identity in a Multicultural Environment - ZHANGUZHIN, Rustem (CENTRAL ASIA AND THE CAUCASUS, 2012)
The subject of my article is relatively novel for Ukraine, a country that has been drawn into the worldwide development of multiculturalism. This means that the academic community should identify the parameters, fundamental features, and characteristics of the related changes In the course of our project we posed ourselves the task of identifying, on the one hand, the basic features of the Ukrainian society conducive to its multicultural format; on the other, the state of diverse ethnocultural groups living in Ukraine and their religious and cultural parameters that make it easier/harder to build up a multicultural society in the republic’s very specific conditions.This article is an attempt at describing the contemporary state of Islam and the specifics of its traditions in Ukraine which should be taken into account when developing multiculturalism. We will clarify the ideology of our project and outline several main specifics and problems of contemporary Muslim identity which serve as the background against which multiculturalism will (or will not, which will entail dangerous repercussions) be formed in Ukraine and which call for profound and detailed analysis.Throughout its history, Ukraine, as part of an associated state structure, has maintained close relations with other countries. Throughout the longest stretch of its history, however, with the exception of short episodes, it remained deprived of the legal rights to be independently and directly involved in international relations. This status, which “truncated” its rights to independent international relations, did not allow Ukraine to regard itself as a de facto/de jure entity of world politics.At the new stage, Ukraine’s recent sovereignty gives it, for the first time in its history, the legitimate right to be involved in international institutions as an independent and fully-fledged entity of international policy. However, the country and its government bodies have to cope with numerous problems, the scope of which has become much wider and calls for well-justified motivations. This constitutes the main specific feature of the new stage.Today, the country’s government bodies are facing the task of working on an algorithm of its own to be applied to systemic problems.